Association between vitamin D deficiency and exercise capacity in patients with CKD, a cross-sectional analysis. Issue 210 (June 2021) - Watson, Emma L.; Wilkinson, Thomas J.; O'Sullivan, Tom F.; Baker, Luke A.; Gould, Douglas W.; Xenophontos, Soteris; Graham-Brown, Matt; Major, Rupert; Jenkinson, Carl; Hewison, Martin; Philp, Andrew; Smith, Alice C.
Highlights: Vitamin D deficiency was highly prevalent in this cohort of non-dialysis dependent CKD patients. There was no association between either total or active vitamin D and muscle size or strength. There was a significant correlation between total vitamin D and VO2Peak . Vitamin D deficiency may play a role in the poor exercise capacity and exercise tolerance seen in these patients. Abstract: Background: Evidence is growing for a role of vitamin D in regulating skeletal muscle mass, strength and functional capacity. Given the role the kidneys play in activating total vitamin D, and the high prevalence of vitamin D deficiency in Chronic Kidney Disease (CKD), it is possible that deficiency contributes to the low levels of physical function and muscle mass in these patients. Methods: This is a secondary cross-sectional analysis of previously published interventional study, with in vitro follow up work. 34 CKD patients at stages G3b-5 (eGFR 25.5 ± 8.3 mL/min/1.73m2; age 61 ± 12 years) were recruited, with a sub-group (n = 20) also donating a muscle biopsy. Vitamin D and associated metabolites were analysed in plasma by liquid chromatography tandem-mass spectroscopy and correlated to a range of physiological tests of muscle size, function, exercise capacity and body composition. The effects of 1α, 25(OH)2D3 supplementation on myogenesis and myotube size was investigated in primary skeletal muscle cells from vitamin D deficient donors. Results: In vivo, there was no association between total or active vitamin D and muscle size or strength, but a significant correlation with V̇O2Peak was seen with total vitamin D (25OHD). in vitro, 1α, 25(OH)2 D3 supplementation reduced IL-6 mRNA expression, but had no effect upon proliferation, differentiation or myotube diameter. Conclusions: Vitamin D deficiency is not a prominent factor driving the loss of muscle mass in CKD, but may play a role in reduced exercise capacity.